Foundation And Education at The Elementary School Level: Bibliometric Analysis - Indrayogi, Indrayogi; Berliana, Berliana; Ma'Mun, Amung; Akinci, Abdullah Yavuz; Triansyah, Andika (Yayasan Keluarga Guru Mandiri, 2025)
This study aims to analyze the development of scientific studies on education at the elementary school level using a bibliometric approach. By utilizing data from various reputable academic databases, this study identifies research trends and the most discussed topics in this field. The methods used include citation analysis, co-word analysis, and network visualization using VOSviewer bibliometric software. This study provides a comprehensive picture by describing descriptive parameters of publications and extracting keywords from authors in the field of Foundations and Education in Elementary schools. This study includes a primer for researchers to gain a better understanding of the progress in scholarly publications related to Foundation Education at the elementary school level. A thorough examination of 266 documents found in the Scopus database was conducted from 2008 to 2024. According to the findings, the number of publications fluctuated, with the highest number of publications occurring between 2008 and 2024, totaling 266 documents. Of these publications, the United States and the United Kingdom were the most productive countries. Overall, research on this topic continues to evolve, with new methods and directions being established. The main contribution of this study is to provide a comprehensive insight into the landscape of basic education research, while identifying research gaps that can form the basis for further studies. The findings also have implications for education policy-making, particularly in developing more effective and evidence-based learning strategies. Thus, this research not only provides a historical overview of the development of basic education studies but also serves as a valuable reference for academics, educators, and policymakers in improving the quality of education at the elementary school level.